Hemigraphis neocaledonica Heine from New Caledonia is transferred to Brunoniella Bremek. (Acanthaceae) - Moylan, E; Scotland, R (2000)
Evidence from macro- and micromorphology is used to clarify the taxonomic position of Hemigraphis neocaledonica Heine, which is here transferred to Brunoniella Bremek. A new combination: Brunoniella neocaledonica (Heine) Moylan is proposed. Brunoniella is a new genus record for New Caledonia. The geographic distribution of Hemigraphis remains unaffected.